Uniform-crystal anti-scaling metal and preparation method thereof

By optimizing the alloy formula and heat treatment process of uniform crystal anti-scaling metal, uniform crystal anti-scaling metal with excellent weather resistance and scale resistance is prepared, which solves the stability and protection of uniform crystal anti-scaling metal in the industrial environment in the prior art. The problem of scale effect achieves efficient and long-term anti-scaling performance.

CN119433284AInactive Publication Date: 2025-02-14ZHEJIANG XINCHENGYUE NEW MATERIAL TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510034276.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing uniform crystal anti-scaling metals are difficult to maintain long-term stability and anti-scaling effect in industrial production environments, and are eroded and damaged by various factors, resulting in a degradation of anti-scaling performance.

Method used

Cu 55~75wt.%, Ni 15~25wt.%, Co 2.0~10.0wt.%, Al 2~5wt.%, Fe 0.5~5.0wt.%, Ce 0.5~0.8wt.%, La 0.3~0.8 The formula of wt.%, Nb 0.025~0.04 wt.%, is prepared by specific heat treatment processes such as heating and smelting, stirring, rapid cooling and annealing treatment to prepare uniform crystal anti-scaling metals with excellent weather resistance and scale resistance.

Benefits of technology

The prepared uniform crystal anti-scaling metal has uniform dendrite structure and uniform distribution of micro-cells, which significantly improves its anti-scaling performance and weather resistance, avoids the problem of excessive zinc and lead, and maintains long-term stability and high efficiency. Anti-scaling effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433284A_ABST
    Figure CN119433284A_ABST
Patent Text Reader

Abstract

The invention discloses a uniform-crystal anti-scaling metal and a preparation method thereof, the uniform-crystal anti-scaling metal comprises, by weight, 55-75% of Cu, 15-25% of Ni, 2.0-10.0% of Co and 0.5-5.0% of Fe, the structure of the obtained anti-scaling alloy is uniform dendritic crystals, microbatteries in the structure are uniformly distributed, and the anti-scaling performance is excellent. The alloy formula is simple in components and free of zinc and lead, and the problems that zinc is dissolved out and lead exceeds the standard of an anti-scaling alloy are completely solved. The alloy performance is synergistically improved by optimizing the alloy types and the using amount in the alloy components, and the content of all elements in the alloy components prepared through the preparation method is meticulously adjusted, so that a good balance state is achieved. The balance state is beneficial for forming a stable alloy structure, and the structure change of the alloy in the preparation and use processes is reduced, so that the stability of the alloy performance is kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anti-scaling metals, and in particular relates to a homogeneous anti-scaling metal and a preparation method thereof. Background Art

[0002] Scaling has always been a common problem in industrial production processes. A typical example is an open-type circulating cooling system, where circulating water is constantly evaporated and lost, and calcium and magnesium ions are concentrated. Scale will gradually precipitate on the heat exchange surface of the heat exchanger or cooler equipment. The scale heat transfer coefficient is only 1% of that of steel, which will cause the heat exchange effect of the equipment to deteriorate. Another example is the oil production system and water injection system, where the liquid mineralization is very high, scaling and waxing problems are very common, which will slowly block the pipeline, causing shutdowns and maintenance, and economic benefits. Loss, especially in some northern regions with hard water or areas where the water source is groundwater. Since calcium, magnesium, silicon, strontium and barium are all scaling elements, in many scenarios, scaling problems are a combination of multiple scaling. Even in the oil field, waxing and scaling problems are often associated problems.

[0003] The formation of inorganic scale usually goes through four processes: polymerization, nucleation, crystal growth, and scaling. When the solute in the solution reaches supersaturation, anions and cations such as Ca 2+ With CO 3 2- / SO 4 2- They collide with each other to form ion pairs, which then form aggregates to become small crystal centers, embryos or micronuclei. These microaggregates become the centers of nucleation and play an important role in nucleation. Microcrystals formed in solution aggregate and / or adsorb to the solid surface, grow into larger microcrystals, and then grow and fuse to form deposited microcrystals. By further adsorbing additional scaling ions in the solution, the formed microcrystals begin to grow continuously and scaling begins to form on the surface.

[0004] Alloy physical anti-scaling technology is a new material water treatment technology that has rapidly emerged in recent years. It achieves anti-scaling, descaling and anti-wax functions through physical principles. It has great technical advantages such as non-magnetic and non-electric, long-lasting, environmentally friendly and maintenance-free. The core is that when the fluid passes through the anti-scaling alloy, the fluid is in full contact with the alloy, which changes the physical properties of the fluid, thereby affecting the crystallization scaling process and achieving the purpose of anti-scaling.

[0005] The core of alloy anti-scaling technology lies in the manufacture and synthesis of alloy materials with excellent anti-scaling function. The performance of homogeneous anti-scaling metal depends to a large extent on its alloy composition. However, there are still certain challenges in optimizing the alloy composition, such as how to accurately control the content and proportion of each element in the alloy to maximize its anti-scaling effect; at the same time, homogeneous anti-scaling metal needs to maintain long-term stability and anti-scaling effect during use. However, due to the complexity and uncertainty of the industrial production environment, homogeneous anti-scaling metal may be corroded and damaged by various factors, resulting in a decrease in its anti-scaling performance. Therefore, how to ensure the long-term stability of homogeneous anti-scaling metal and how to carry out effective maintenance and management are also technical problems that need to be solved at present. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a homogeneous anti-scaling metal.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising: Cu 55~75wt.%, Ni 15~25wt.%, Co 2.0~10.0wt.%, Al 2~5wt.%, Fe 0.5~5.0wt.%, Ce 0.5~0.8wt.%, La 0.3~0.8wt.%, Nb 0.025~0.04wt.%.

[0010] As a preferred embodiment of the homogeneous anti-scaling metal of the present invention, it includes, by mass percentage, Cu 67 wt.%, Ni 21 wt.%, Co 4.5 wt.%, Al 3.5 wt.%, Fe 2.5 wt.%, Ce 0.8 wt.%, La 0.67 wt.%, and Nb 0.03 wt.%.

[0011] Another object of the present invention is to provide a method for preparing homogeneous anti-scaling metal.

[0012] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising: The raw materials Cu and Ni are put into a graphite crucible with a quartz protective sleeve, and the graphite crucible is placed on a high-frequency induction furnace, heated to remove moisture, and then heated to melt. After the raw materials Cu and Ni are completely melted, they are stirred and kept warm to form a first melt; Adding preheated and dried raw materials Co, Al, Fe, Ce, La, and Nb to the first melt, keeping the mixture warm and stirring to form a second melt; The second melt is quickly cooled and poured into a sand mold after the scum is removed. After solidification, it is naturally cooled to obtain an ingot, and annealing treatment is performed to form a homogeneous anti-scaling metal.

[0013] As a preferred embodiment of the method for preparing the homogeneous anti-scaling metal of the present invention, the heating temperature of the heating smelting is 1400-1480°C.

[0014] As a preferred embodiment of the method for preparing the homogeneous anti-scaling metal of the present invention, the heating rate of the heating smelting is 45-55°C / h.

[0015] As a preferred solution of the method for preparing the homogeneous anti-scaling metal of the present invention, a charcoal covering agent is added to cover the raw materials during the heating and smelting process.

[0016] As a preferred solution of the method for preparing the homogeneous anti-scaling metal of the present invention, the insulation temperature of the insulation and static state is 1400-1480°C.

[0017] As a preferred solution of the method for preparing the homogeneous anti-scaling metal of the present invention, the second melt is rapidly cooled to 1200-1250°C.

[0018] As a preferred embodiment of the method for preparing the homogeneous anti-scaling metal of the present invention, the annealing temperature of the annealing treatment is 800-900°C.

[0019] As a preferred embodiment of the method for preparing the homogeneous anti-scaling metal of the present invention, the annealing time of the annealing treatment is 2 to 4 hours.

[0020] Beneficial effects of the present invention: The present invention provides a homogeneous anti-scaling metal with excellent weather resistance and scale inhibition. The obtained anti-scaling alloy structure is a uniform dendrite, the micro-batteries in the structure are evenly distributed, and the anti-scaling performance is excellent. The anti-scaling components in the alloy formula are simple, do not contain zinc and lead, and completely avoid the problems of zinc dissolution and excessive lead in the anti-scaling alloy. By optimizing the type and amount of alloy in the alloy components and synergistically improving the alloy performance, the content of each element in the alloy components obtained by the present invention is carefully formulated to achieve a good balance state. This equilibrium state helps to form a stable alloy organizational structure, reduce organizational changes in the alloy during preparation and use, and thus maintain the stability of the alloy performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them: Figure 1 Schematic diagram of the metallographic structure of the alloy prepared in Example 1 of the present invention.

[0022] Figure 2 This is a schematic diagram of the SEM image of the scale deposits on the coupon (control group) without the anti-scaling alloy.

[0023] Figure 3 This is a schematic diagram of the scale deposited on the hanging piece after using the anti-scaling alloy prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0024] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0025] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0026] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0027] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art, and the purity of the raw materials is >99.9%.

[0028] The weather resistance test of the homogeneous anti-scaling metal prepared in the present invention refers to the following method: 100 g of the anti-scaling alloy block prepared in the example / comparative example was placed in 650° C. steam, and the mass change data of the steam oxidation test for 1000 h was calculated. The lower the mass change, the better the weather resistance.

[0029] The anti-scaling rate test of the homogeneous anti-scaling metal prepared in the present invention refers to the following method: 100g of the anti-scaling alloy block prepared in the embodiment / comparative example was placed in a 1000ml beaker containing the experimental water sample, and a blank control experimental beaker (without the anti-scaling alloy block) was set up; The same number of stainless steel 316L hanging pieces were hung in the beakers of the experimental group and the blank control group. The mass of the stainless steel hanging pieces in each group of beakers was weighed before the experiment. The hanging time was 168 hours. The stainless steel hanging pieces were taken out after 168 hours. The weight of the stainless steel hanging pieces at the end of the experiment was tested respectively, and the weight gain rate of the hanging pieces was calculated, which was recorded as the anti-scaling rate. The anti-scaling rate calculation formula is: Anti-scaling rate = [(weight difference of stainless steel coupons in the control group after the experiment - weight difference of stainless steel coupons with anti-scaling alloys of the embodiment / comparative example after the experiment) / weight difference of stainless steel coupons in the control group after the experiment)] × 100% The simulated water quality used in this experiment is shown in Table 1 below: Table 1 Experimental water quality parameters Example 1

[0030] This embodiment provides a method for preparing a homogeneous anti-scaling metal, specifically: The raw materials were weighed according to the following composition: Cu 67 wt.%, Ni 21wt.%, Co 4.5wt.%, Al 3.5wt.%, Fe2.5wt.%, Ce 0.8wt.%, La 0.67wt.%, and Nb 0.03wt.%.

[0031] 2) The raw materials Cu and Ni are put into a graphite crucible with a quartz protective sleeve, and the graphite crucible is placed on a high-frequency induction furnace, preheated at 250°C for 20 minutes, and the water in the crucible is removed and then heated for smelting. During this smelting process, a charcoal covering agent is added to ensure that the surface of the molten metal is covered with charcoal to isolate the air. The heating rate is 50°C / h, and the temperature is raised to 1450°C. After the raw materials Cu and Ni are completely melted, they are stirred and kept warm for 10 minutes to form a first melt; Add the raw materials Co, Al, Fe, Ce, La and Nb which are preheated and dried at 150°C for 30 minutes to the first melt which is stabilized at 1450°C, keep the mixture at the temperature for 10 minutes, and stir it for 2 minutes to form a second melt; The second melt is rapidly cooled to 1200°C, the scum on the surface of the melt is removed, the crucible is taken out and the melt is rapidly poured into a sand mold, and after solidification, it is naturally cooled to obtain an ingot; After the ingot is cleaned from sand, it is homogenized and annealed at 850℃ in a box-type annealing furnace for 3 hours to form a homogeneous anti-scaling metal.

[0032] Figure 1This is a schematic diagram of the gold phase structure of the homogeneous anti-scaling metal prepared in this embodiment. It can be seen that the anti-scaling alloy structure is uniform dendrites, and the micro-batteries in the structure are evenly distributed, ensuring its excellent anti-scaling performance.

[0033] Figure 2 This is a schematic diagram of the SEM of the scale deposits on the coupons of the control group during the anti-scaling rate test. Figure 3 Schematic diagram of the SEM of the scale deposited on the hanging piece containing the anti-scaling alloy of this embodiment. It can be seen that the anti-scaling alloy prepared in this embodiment has a significant anti-scaling effect. Example 2

[0034] The difference between this embodiment and embodiment 1 is that the raw material formula is adjusted to: Cu 55 wt.%, Ni 26wt.%, Co 10 wt.%, Al 2.5wt.%, Fe 5.0wt.%, Ce 0.67wt.%, La0.8wt.%, Nb 0.03wt.%; the remaining steps and processes are all referred to Example 1 to obtain the anti-scaling alloy of this comparative example. Example 3

[0035] The difference between this embodiment and embodiment 1 is that the raw material formula is adjusted to: Cu 75 wt.%, Ni 15wt.%, Co 2wt.%, Al 2.5wt.%, Fe 4.0wt.%, Ce 0.8wt.%, La0.67wt.%, Nb 0.03wt.%; the remaining steps and processes are all referred to Example 1 to obtain the anti-scaling alloy of this comparative example. Example 4

[0036] The difference between this embodiment and embodiment 1 is that the raw material formula is adjusted to: Cu 65 wt.%, Ni 20 wt.%, Co 5 wt.%, Al 4.5 wt.%, Fe 4.0 wt.%, Ce 0.78 wt.%, La 0.7 wt.%, Nb 0.02 wt.%, and the remaining steps and processes are the same as those in Example 1 to obtain the anti-scaling alloy of this comparative example.

[0037] Comparative Example 1

[0038] The difference between this comparative example and Example 1 is that the raw material formula is adjusted to: Cu 70 wt.%, Ni 21 wt.%, Co 4.5 wt.%, Fe 2.5 wt.%; the remaining steps and processes are all referred to Example 1 to obtain the anti-scaling alloy of this comparative example.

[0039] The weather resistance and scale inhibition rate of the anti-scaling alloys obtained in Examples 1 to 4 and Comparative Example 1 were measured, and the results are shown in Table 2.

[0040] Table 2 <![CDATA[Weather resistance (mg / cm 2 )]]> Scale inhibition rate / % Example 1 0.0816 98 Example 2 0.9012 96 Example 3 0.1365 94 Example 4 0.1120 95 Comparative Example 1 2.6240 66 It can be seen from Table 1 that the anti-scaling alloy prepared by compounding the components of the embodiments of the present invention has good weather resistance and scale inhibition rate. The present invention adds elements such as Al, Ce, La, etc. to the anti-scaling metal, which not only enhances the antioxidant and corrosion resistance of the material, but also forms stable compounds by reacting with minerals in water to inhibit scale formation; at the same time, the addition of these elements and Nb optimizes the microstructure of the material, refines the grains, improves the phase distribution, and thus improves the overall stability and mechanical properties, and jointly promotes the significant improvement of weather resistance and scale inhibition rate through the improvement of surface properties.

[0041] Comparative Example 2

[0042] The difference between this comparative example and Example 1 is that the Al component is omitted, and the raw material formula is adaptively adjusted to: Cu 70wt.%, Ni 21wt.%, Co 5wt.%, Fe 2.5wt.%, Ce 0.8wt.%, La 0.67wt.%, Nb 0.03wt.%, and the remaining steps and processes are referred to Example 1 to obtain the anti-scaling alloy of this comparative example.

[0043] Comparative Example 3

[0044] The difference between this comparative example and Example 1 is that the Ce component is omitted, and the raw material formula is adaptively adjusted to: Cu 67wt.%, Ni 21wt.%, Co 4.5wt.%, Al 4.0wt.%, Fe 2.8wt.%, La 0.67wt.%, Nb 0.03wt.%, and the remaining steps and processes are referred to Example 1 to obtain the anti-scaling alloy of this comparative example.

[0045] Comparative Example 4

[0046] The difference between this comparative example and Example 1 is that the La component is omitted, and the raw material formula is adaptively adjusted to: Cu 67wt.%, Ni 21wt.%, Co 4.5wt.%, Al 3.8wt.%, Fe 2.87wt.%, Ce 0.8wt.%, Nb 0.03wt.%, and the remaining steps and processes are referred to Example 1 to obtain the anti-scaling alloy of this comparative example.

[0047] Comparative Example 5

[0048] The difference between this comparative example and Example 1 is that the Nb component is omitted, and the raw material formula is adaptively adjusted to: Cu 67wt.%, Ni 21wt.%, Co 4.5wt.%, Al 3.5wt.%, Fe 2.5wt.%, Ce 0.8wt.%, La 0.70wt.%, and the remaining steps and processes are referred to Example 1 to obtain the anti-scaling alloy of this comparative example.

[0049] The weather resistance and scale inhibition rate of the anti-scaling alloys obtained in Comparative Examples 2 to 5 were measured and compared with those in Example 1. The results are shown in Table 3.

[0050] Table 3 <![CDATA[Weather resistance (mg / cm 2 )]]> Scale inhibition rate / % Example 1 0.0816 98 Comparative Example 2 1.7251 83 Comparative Example 3 1.8814 73 Comparative Example 4 1.7652 85 Comparative Example 5 1.5236 90 As can be seen from Table 3, the good weather resistance and scale inhibition of the alloy prepared by the present invention are largely due to the synergistic effect between the components. Among them, the Al element not only enhances the corrosion resistance and oxidation resistance of the alloy, but also protects the matrix through the stable compounds formed, while optimizing the surface properties and reducing the adhesion of scale. Ce and La, as rare earth elements, not only form a dense oxide film that effectively resists corrosion, but also refine the grains, improve the microstructure, and further enhance the mechanical properties and weather resistance of the alloy. In addition, they can also indirectly improve the scale inhibition performance by changing the crystal structure and growth process of scale.

[0051] The addition of Nb improves the thermal stability and high-temperature strength of the alloy, refines the grains, and improves the microstructure. However, when the key components Al, Ce, La, and Nb are omitted respectively, the interactions in the alloy are broken, resulting in a significant decrease in weather resistance and scale inhibition. Specifically, omitting Al weakens the corrosion resistance of the alloy, reduces weather resistance, and may affect the scale inhibition performance; omitting Ce and La destroys the oxidation resistance and corrosion resistance, reduces weather resistance, and may affect the scale formation process; omitting Nb reduces the thermal stability and high-temperature strength of the alloy, further affecting weather resistance. Therefore, these elements play an indispensable role in the alloy, and their presence and interaction jointly determine the excellent performance of the alloy. Example 5

[0052] The difference between this embodiment and embodiment 1 is that the amount of Al is adjusted to 0.5, 1, 3.5, and 6%, respectively, and the amount of Cu is adaptively adjusted so that the total amount of raw material components is 100wt.%. The remaining steps and processes are referred to embodiment 1 to obtain anti-scaling alloys with different Al contents in this embodiment.

[0053] The weather resistance and scale inhibition rate of anti-scaling alloys with different Al contents were compared. The results are shown in Table 4.

[0054] Table 4 Al content <![CDATA[Weather resistance (mg / cm 2 ).]]> Scale inhibition rate / % 0.5wt.% 1.5261 84 1wt.% 1.3245 88 3.5wt.% 0.0816 98 6wt.% 1.6520 90 It can be seen from Table 4 that different Al contents have a significant effect on the weather resistance and scale inhibition rate of the anti-scaling alloy. The Al element can usually refine the grains in the alloy. When its content is too low, the refinement effect may not be obvious, resulting in a relatively large grain size of the alloy, which in turn affects the mechanical properties of the alloy. When the content is too high, it will lead to too many Al-rich areas in the alloy structure, forming a phase structure that is not conducive to the performance of the alloy, and may even cause abnormal growth of the grains, making the alloy more susceptible to corrosion in harsh environments.

[0055] Aluminum in alloys may inhibit scale formation by forming specific compounds or adsorbing on the alloy surface. The scale inhibition effect of aluminum in alloys mainly depends on its adsorption and compound formation ability on the alloy surface. When the aluminum content is too low, these abilities may be significantly weakened, resulting in an incomplete or unstable scale inhibition layer on the alloy surface, making the alloy more likely to react adversely with minerals in water to form compounds that promote scale formation. However, when the aluminum content is too high, the stability and uniformity of these compounds or adsorption layers will be affected, thereby reducing the scale inhibition performance of the alloy. Example 6

[0056] The difference between this embodiment and embodiment 1 is that the amount of Ce is adjusted to 0.1, 0.3, 0.8, and 1.2%, respectively, and the amount of Cu is adaptively adjusted so that the total amount of raw material components is 100wt.%. The remaining steps and processes are referred to embodiment 1 to obtain anti-scaling alloys with different Ce contents in this embodiment.

[0057] The weather resistance and scale inhibition rate of anti-scaling alloys with different Ce contents were compared. The results are shown in Table 5.

[0058] Table 5 Ce content <![CDATA[Weather resistance (mg / cm 2 )]]> Scale inhibition rate / % 0.1wt.% 1.7168 80 0.3wt.% 1.6012 86 0.8wt.% 0.0816 98 1.2wt.% 1.4520 89 In the scheme of the present invention, an appropriate amount of Ce can refine the grains of the alloy and reduce defects at the grain boundaries, thereby improving the weather resistance of the alloy. When the Ce content is too low, this refinement effect is not obvious, the grains of the alloy may be larger, and the defects at the grain boundaries increase, resulting in reduced weather resistance. When the Ce content is reduced from 0.8% to 0.1%, the number of Ce compounds in the alloy decreases. These compounds usually have low electrochemical activity and can form a protective layer on the surface of the alloy to resist corrosion by corrosive media. Therefore, too low a Ce content will lead to a decrease in the scale inhibition rate of the alloy.

[0059] When the Ce content is too high, a large amount of Ce compounds will be formed. These compounds may consume other elements in the alloy (such as Al), causing changes in the microstructure of the alloy and segregation. That is, the Ce compounds are unevenly distributed in the alloy. This segregation phenomenon may make the alloy more susceptible to corrosion in corrosive media, thereby reducing weather resistance; and too many Ce compounds can form a continuous network structure, which may reduce the toughness and plasticity of the alloy, making it more susceptible to cracks and fractures under stress, thereby reducing weather resistance. Example 7

[0060] The difference between this embodiment and embodiment 1 is that the amount of La is adjusted to 0.2, 0.67, 0.9, and 1.2w%, respectively, and the amount of Cu is adaptively adjusted so that the total amount of raw material components is 100wt.%. The remaining steps and processes are referred to embodiment 1 to obtain anti-scaling alloys with different La contents in this embodiment.

[0061] The weather resistance and scale inhibition rate of anti-scaling alloys with different La contents were compared, and the results are shown in Table 6.

[0062] Table 6 La content <![CDATA[Weather resistance (mg / cm 2 )]]> Scale inhibition rate / % 0.2wt.% 1.6138 87 0.67wt.% 0.0816 98 0.9wt.% 1.4528 92 1.2wt.% 1.6208 88 In the present invention, the La element is added to improve the oxidation resistance of the alloy, reduce the oxide shedding during the oxidation process, and thus improve the weather resistance of the alloy. When the La content is too low (such as 0.2%), this antioxidant effect is weakened, and the alloy is more susceptible to corrosion in an oxidizing environment, resulting in a decrease in weather resistance. The La element can usually improve the oxidation resistance of the alloy and reduce the oxide shedding during the oxidation process, thereby increasing the service life of the alloy. When the La content is too low (such as 0.2%), this antioxidant effect is weakened, and the alloy is more susceptible to corrosion in an oxidizing environment, resulting in a decrease in weather resistance. Too much La compounds may form blocky precipitates, and these structures are prone to become crack sources under stress, reducing the toughness and plasticity of the alloy, making it more susceptible to damage in harsh environments.

[0063] In addition, La and Al can form stable compounds, such as Al-La phases, which usually have low electrochemical activity and can form a protective layer on the alloy surface to improve the corrosion resistance of the alloy. However, when the La content is too high, too much Al-La phase may be formed, resulting in a reduction in the Al element in the alloy, thus affecting the weather resistance and scale resistance of the alloy.

[0064] In summary, the present invention provides a homogeneous anti-scaling metal with excellent weather resistance and scale resistance. By optimizing the alloy type and amount in the alloy component, the alloy performance is synergistically improved. In the formula of the present invention, Cu and Ni are both important elements for improving the corrosion resistance of the alloy. Cu itself has good corrosion resistance, and Ni can further enhance the corrosion resistance of the alloy in various environments. The combination of the two can form a stable alloy structure, reduce the erosion of the alloy by the corrosive medium, and the Al element can form a dense oxide protective film in the alloy to improve the weather resistance of the alloy.

[0065] Ce and La, as rare earth elements, can refine the grains of the alloy and reduce defects at the grain boundaries, thereby further improving the corrosion resistance of the alloy. At the same time, Ce and La can also form stable compounds with Al to enhance the stability of the protective film. Cu, Ni and Co are all solid solution strengthening elements. They can be dissolved in the alloy matrix to improve the strength and hardness of the alloy. At the same time, Ni and Co can also improve the toughness of the alloy, making it less prone to brittle fracture when the alloy is subjected to stress; Nb, as a microalloying element, can refine the grains of the alloy and improve the strength and toughness of the alloy. This refinement effect helps the alloy maintain stable performance when subjected to high stress; Ce and La elements can absorb minerals in water in the alloy and inhibit the formation of scale. At the same time, they can also form compounds with other elements in the alloy. These compounds have low electrochemical activity and can reduce the reaction between the alloy and minerals in water, thereby improving the scale inhibition performance of the alloy.

[0066] The content of each element in the alloy component prepared by the present invention is carefully adjusted to achieve a good balance state. This balance state helps to form a stable alloy structure, reduce the structural changes of the alloy during preparation and use, and thus maintain the stability of the alloy performance.

[0067] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A homogeneous anti-scaling metal, characterized in that: In percentage by mass, including: Cu 55~75wt.%, Ni 15~25wt.%, Co 2.0~10.0wt.%, Al 2~5wt.%, Fe 0.5~5.0wt.%, Ce0.5~1wt.%, La 0.3~0.8wt.%, Nb 0.025~0.04wt.%.

2. The homogeneous anti-scaling metal according to claim 1, characterized in that: In terms of mass percentage, it includes Cu 67wt.%, Ni 21wt.%, Co 4.5wt.%, Al 3.5wt.%, Fe 2.5wt.%, Ce 0.8wt.%, La 0.67wt.%, and Nb0.03wt.%.

3. The method for preparing a homogeneous anti-scaling metal according to claim 1, characterized in that: include, The raw materials Cu and Ni are put into a graphite crucible with a quartz protective sleeve, and the graphite crucible is placed on a high-frequency induction furnace, heated to remove moisture, and then heated to melt. After the raw materials Cu and Ni are completely melted, they are stirred and kept warm to form a first melt; Adding preheated and dried raw materials Co, Al, Fe, Ce, La, and Nb to the first melt, keeping the mixture warm and stirring to form a second melt; The second melt is quickly cooled and poured into a sand mold after the scum is removed. After solidification, it is naturally cooled to obtain an ingot, and annealing treatment is performed to form a homogeneous anti-scaling metal.

4. The method for preparing a homogeneous anti-scaling metal according to claim 3, characterized in that: The heating temperature of the heating smelting is 1400-1480°C.

5. The method for preparing a homogeneous anti-scaling metal according to claim 4, characterized in that: The heating rate of the heating smelting is 45-55°C / h.

6. The method for preparing a homogeneous anti-scaling metal according to claim 5, characterized in that: During the heating and smelting process, a charcoal covering agent is added to cover the raw materials.

7. The method for preparing a homogeneous anti-scaling metal according to claim 3, characterized in that: The heat preservation temperature of the heat preservation and static placement is 1400-1480°C.

8. The method for preparing a homogeneous anti-scaling metal according to claim 3, characterized in that: The second melt is rapidly cooled to 1200-1250°C.

9. The method for preparing a homogeneous anti-scaling metal according to claim 3, characterized in that: The annealing temperature of the annealing treatment is 800-900°C.

10. The method for preparing a homogeneous anti-scaling metal according to claim 9, characterized in that: The annealing time of the annealing treatment is 2 to 4 hours.

Citation Information

Patent Citations

  • High-strength wear-resistant copper alloy and preparation method thereof

    CN104164589A

  • All-intelligent water pre-purification scale preventer

    CN107188347A

  • Full-intelligent scale-preventing and scale-removing alloy and preparation method thereof

    CN107338368A

  • Preparation method of corrosion-resistant Cu-Ni alloy

    CN110205515A

  • Copper-nickel-tin alloy and preparation method thereof

    CN115710654A